Development and validation of a rapid chromatographic method for the analysis of flunarizine and its main production impurities - Niamh OâConnor; Michael Geary; Mary Wharton; Paul Sweetman (Elsevier, 2013)
A rapid selective method for the analysis of flunarizine and its associated impurities was developed and validated according to ICH guidelines. The separation was carried out using a Thermo Scientific Hypersil Gold C18 column (50mmÃ4.6mm i.d., 1.9Î¼m particle size) with a gradient mobile phase of acetonitrileâammonium acetateâtetrabutylammoniumhydrogen sulfate buffer, at a flow rate of 1.8mL/min and UV detection at 230nm. Naturally aged samples were also tested to determine sample stability. A profile of sample and impurity breakdown was also presented. Keywords: Flunarizine, Sub 2Î¼m column, Active pharmaceutical ingredient, HPLC